SARS-CoV-2 decreases malaria severity in co-infected rodent models - Fraga, Ana; Mósca, Andreia F.; Moita, Diana; Simas, J. Pedro; Nunes-Cabaço, Helena; Prudêncio, Miguel (Frontiers in Cellular and Infection Microbiology, 2023)
Coronavirus disease 2019 (COVID-19) and malaria, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and Plasmodium parasites, respectively, share geographical distribution in regions where the latter disease is endemic, leading to the emergence of co-infections between the two pathogens. Thus far, epidemiologic studies and case reports have yielded insufficient data on the reciprocal impact of the two pathogens on either infection and related diseases. We established novel co-infection models to address this issue experimentally, employing either human angiotensin-converting enzyme 2 (hACE2)expressing or wild-type mice, in combination with human-or mouse-infective variants of SARS-CoV-2, and the P. berghei rodent malaria parasite. We now show that a primary infection by a viral variant that causes a severe disease phenotype partially impairs a subsequent liver infection by the malaria parasite. Additionally, exposure to an attenuated viral variant modulates subsequent immune responses and provides protection from severe malariaassociated outcomes when a blood stage P. berghei infection was established. Our findings unveil a hitherto unknown host-mediated virus-parasite interaction that could have relevant implications for disease management and control in malaria-endemic regions. This work may contribute to the development of other models of concomitant infection between Plasmodium and respiratory viruses, expediting further research on co-infections that lead to complex disease presentations.